Artisans in Early Imperial China - Mcquaide, Shiling (Labour / Le Travail, 2009)
The article reviews the book, "Artisans in Early Imperial China," by Anthony J. Barbieri-Low.
Keywords: ARTISANS – History; ARTISANS in Early Imperial China (Book); Ancient civilizations; BARBIERI-Low; Anthony J.; BOOKS – Reviews; Book reviews; Business And Economics–Labor And Industrial Relations; Craftsmen; History–History of North And South America; Nonfiction